The impact of mathematical modeling on the understanding of diabetes and related complications. (10th July 2013) - Ajmera, I; Swat, M; Laibe, C; Le Novère, N; Chelliah, V
Abstract : Diabetes is a chronic and complex multifactorial disease caused by persistent hyperglycemia and for which underlying pathogenesis is still not completely understood. The mathematical modeling of glucose homeostasis, diabetic condition, and its associated complications is rapidly growing and provides new insights into the underlying mechanisms involved. Here, we discuss contributions to the diabetes modeling field over the past five decades, highlighting the areas where more focused research is required. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e54; doi:10.1038/psp.2013.30 ; advance online publication 10 July 2013